Managerial Practices and Students' Performance - Adriana Di Liberto; Fabiano Schivardi; Giovanni Sulis (Institute for the Study of Labor (IZA), 2014)
We study the effects of managerial practices in schools on students' outcomes. We measure managerial practices using the World Management Survey, a methodology that enables us to construct robust measures of management quality comparable across countries. We find substantial heterogeneity in managerial practices across six industrialized countries, with more centralized systems (Italy and Germany) lagging behind the more autonomous ones (Canada, Sweden, the UK, the US). For Italy, we are able to match organizational practices at the school level with students' outcomes in a math standardized test. We find that managerial practices are positively related to students' outcomes. The estimates imply that if Italy had the same managerial practices as the UK (the best performer), it would close the gap in the math OECD-PISA test with respect to the OECD average. We argue that our results are robust to selection issues and show that they are confirmed by a set of IV estimates and by a large number of robustness checks. Overall, our results suggest that policies directed at improving students' cognitive achievements should take into account principals' selection and training in terms of managerial capabilities.
Keywords: L2; I2; M1; O32; 330; management; productivity; school principals; cognitive skills